PENGARUH KEPEMIMPINAN, MOTIVASI, DAN LINGKUNGAN TERHADAP KINERJA PEGAWAI (Studi Pada Dinas Perhubungan Kota Semarang) - Shinta Lestari, 15.05.51.0130; Rahayuningsih, sri (Students' Journal of Economic and Management, 2019)
This study analyzes the influence of leadership, motivation and work environment on employee performance. The object of research in this paper is the Semarang City Office of Transportation, the sampling technique in this study was using purposive sampling amounting to 60 respondents as samples with data collection methods using questionnaires by distributing a list of statements to respondents to obtain information. The research objective was formulated to determine the effect of leadership, motivation and work environment on employee performance. Analysis of the data used included, test factor analysis to test the validity of question items, cronbach alpha formula to test the reliability of each independent variable tested by regression analysis. The results of the research are: (1) Leadership has a positive and significant influence on employee performance. (2) Motivation has a positive and significant influence on employee performance. (3) Work Environment has a positive and significant influence on employee performance.